Impact of Social Responsibility Programmes in Stakeholder Satisfaction: An Empirical Study of Portuguese Managers’ Perceptions - Fonseca, Luís (2012)
This study investigates the relationship between social responsibility programmes of organizations and stakeholder satisfaction. Based on stakeholder theory, an online survey was administered to managers of Portuguese organizations with certified management systems. The findings suggest that stakeholder satisfaction is indeed increased with a social responsibility programme, as suggested by Freeman’s stakeholder theory. The components of social responsibility programmes that we discussed in this paper comprehend, among others, the “best governance practices”, “best customers, suppliers and partners management practices” and “best social inclusion and society support and relationship practices”, and do provide a balanced and continuously satisfaction to the different sets of stakeholders as shown by our survey results.